EXPERIMENTAL EVALUATION OF WHEAT GRAIN MOISTURE RESPONSE TO AERODYNAMIC REGIMES - Azizjon Isomidinov; Abdullox Abdulazizov; Alisher Abdukadirov (Modern American Journals, 2025)
This paper presents the results of an experimental investigation into how changes in wheat grain moisture content depend on aerodynamic drying conditions. The experiments were carried out in a vertical cascading dryer, using air heated to 60–80 °C (preheated up to 90 °C in a calorifier) as the thermal agent. The main parameters examined were air velocity (υ = 5–20 m/s), dryer productivity (Q = 0.06–0.07 kg/s), and the number of cascade stages (4, 6, and 8). The dryer contained five heat-exchange zones, and the initial grain moisture content was 22%. The findings demonstrated that the moisture reduction process in wheat grains is strongly influenced by changes in the aerodynamic regime. The obtained results are of practical importance for optimizing the parameters of thermal agents and improving the overall efficiency of the drying process.
Keywords: Wheat, drying, aerodynamic regime, heat agent, moisture, cascading dryer, efficiency.